Impact of Assurance and Assurer's Professional Affiliation on Financial Analysts' Assessment of Credibility of Corporate Social Responsibility Information - Pflugrath, Gary; Roebuck, Peter; Simnett, Roger (Auditing : a journal of practice and theory, 2011)
This study reports the results of a behavioral experiment examining whether financial analysts from Australia, the United States, and the United Kingdom perceive a difference in the credibility of stand-alone corporate social responsibility (CSR) reports depending on whether they are assured, and the type of assurance provider (professional accountants versus sustainability consultants). We further examine whether the perceived credibility differs for financial analysts from the different countries and whether results hold for companies from different industries. The overall results show the credibility of a CSR report is greater when it is assured and when the assurer is a professional accountant. While assurance increases the credibility of the information in each of the three countries included, the relative impact is context-specific. Information is perceived to be more credible when a company is from an industry where assurance is more commonplace, and by financial analysts from the United States when the assurer is a professional accountant. Financial analysts from Australia and the United Kingdom perceive little difference in the enhanced credibility provided by the different assurance providers. Data Availability: Contact the first author about the availability of the data.